Airborne gravity gradiometer surveying of petroleum systems under Lake Tanganyika, Tanzania. Issue 3 (1st September 2016) - Roberts, Doug; Chowdhury, Priyanka Roy; Lowe, Sharon Jenny; Christensen, Asbjorn Norlund
Abstract : The Lake Tanganyika South petroleum exploration block covers the southern portion of the Tanzanian side of Lake Tanganyika and is located within the East African Rift System. The rifting process has formed rotated fault blocks which provide numerous play types in the resulting basins. Interpretation of 2D seismic data from 1984 indicated that sufficient sediment thickness is present for hydrocarbon generation. The prospectivity of the lake sediment sequence is enhanced by large oil discoveries further north along the rift system at Lake Albert in Uganda. Airborne gravity gradiometry (AGG) has been used in the Lake Albert region to delineate the structural framework of sedimentary basins. Based on this analogy, in 2010 Beach Energy commissioned CGG to fly a FALCON AGG and high-resolution airborne magnetic survey over the Lake Tanganyika South block to provide data for mapping the basin architecture and estimating the depth to magnetic basement. A total of nearly 28000 line kilometres of data were acquired. The subsequent interpretation incorporated the AGG and magnetic data with available 2D seismic data, elevation model data, bathymetry, Landsat and regional geology information. The integrated data interpretation revealed that the Lake Tanganyika rifting structures occur as half-grabens that were formed through reactivation of Precambrian fault structures. Two major depocentres were identified in the magnetic depth-to-basement map in the north and in the west-central part of the survey area with sediment thicknesses in excess of 4 km and 3 km, respectively. Smaller, shallower depocentres (with less than 3 km of sediment) occur in the south-western region. This information was used to plan a 2100 km 2D marine seismic survey that was recorded in 2012. An interpretation of the results from the seismic survey confirmed a rifting structure similar to that encountered further north at Lake Albert in Uganda. Several targets were identified from the seismic sections for follow-up. Abstract : An airborne gravity gradiometry and high-resolution aeromagnetic survey conducted in Lake Tanganyika within the East African Rift System has been interpreted to demonstrate sedimentary sequences and structures prospective for petroleum. Numerous play types analogous to the Lake Albert oil discoveries further north in Uganda are revealed by further surveys.